2020
DOI: 10.1021/acs.langmuir.0c01571
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Stability and Redispersibility of Mesoporous Silica Nanoparticles in Biological Media

Abstract: The outreach of nanoparticle-based medical treatments has been severely hampered due to the imbalance between the efforts in designing extremely complex materials and the general lack of studies devoted to understanding their colloidal stability in biological environments. Over the years, the scientific community has neglected the relevance related to the nanoparticles’ colloidal state, which consequently resulted in very poor bench-to-clinic translation. In this work, we show how mesoporous silica nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…The overall colloidal stability of bare HfO 2 NPs in the present study may have also been aided by a mesoporous structure observed in TEM (Figure 2(c)), which decreases the effective NP mass density and increases the specific surface area. These effects have been previously observed in mesoporous silica NPs over a wide size range (~50–350 nm) 31‐33 . For comparison, bare HfO 2 NPs (~10–30 nm in size) previously prepared by a sol–gel synthesis in our laboratory sedimented within minutes in water and were thus stabilized by molecular surface functionalization 6 …”
Section: Discussionmentioning
confidence: 52%
“…The overall colloidal stability of bare HfO 2 NPs in the present study may have also been aided by a mesoporous structure observed in TEM (Figure 2(c)), which decreases the effective NP mass density and increases the specific surface area. These effects have been previously observed in mesoporous silica NPs over a wide size range (~50–350 nm) 31‐33 . For comparison, bare HfO 2 NPs (~10–30 nm in size) previously prepared by a sol–gel synthesis in our laboratory sedimented within minutes in water and were thus stabilized by molecular surface functionalization 6 …”
Section: Discussionmentioning
confidence: 52%
“…Second, depending on the size, shape, and surface chemistry, the fate of the designed formulation is correlated to the success of the delivery system. Among such various features, colloidal stability of the nanoformulation plays a crucial role in the dosage distribution and their fate in the systemic circulation, delivery patterns, and eventual clearance [ 294 , 425 , 428 , 429 ]. MSNs are generally negative in charge and stable in physiological fluids, which has limited their successful delivery as the biological membranes possess negative charge, resulting in repulsion and poor delivery.…”
Section: Discussionmentioning
confidence: 99%
“…For biomedical applications, MSNs possess advantageous properties, such as high biocompatibility, , biodegradability in the cell membranes, high thermal and colloidal stability, large internal/external surface area (>700 m 2 /g), and pore volume (4.5 cm 3 /g) . On top of that, the possibility to tune pore size (2–50 nm), pore structure ( e.g.…”
Section: Silica-based Nanomaterialsmentioning
confidence: 99%
“…26 The most prominent example of silica materials are mesoporous silica nanoparticles (MSNs), which are porous structures containing periodically ordered mesopores. 27 For biomedical applications, MSNs possess advantageous properties, such as high biocompatibility, 28,29 biodegradability in the cell membranes, 30 high thermal and colloidal stability, 31 large internal/external surface area (>700 m 2 /g), 32 and pore volume (4.5 cm 3 /g). 33 On top of that, the possibility to tune pore size (2−50 nm), 34 pore structure (e.g., hexagonal, cubic, concentric, foam-like, and worm-like), 22 and morphology (e.g., spherical, hollow, prismatic, toroidal, and rod-shaped) 35 directly influences the cellular uptake and internalization rates and mediates biological effects.…”
Section: Silica-based Nanomaterialsmentioning
confidence: 99%